Sociodemographic and personal factors related to depressive symptomatology in the Mexican population aged 12 to 65 - Fleiz Bautista,Clara (2012)
OBJECTIVE: To describe the prevalence of depressive symptoms in the Mexican population, aged 12 to 65 years, by identifying the main related socio-demographic and personal factors. METHODS: Data are drawn from the National Survey on Addictions 2008 (ENA 2008), a random, probabilistic, multistage study. A randomly selected sub-sample of 22,962 persons answered the section on depressive symptomatology, measured with the Center for Epidemiologic Studies Depression Scale (CES-D). RESULTS: The total prevalence for depressive symptomatology was 5.1%; the prevalence was 7.5% for women and 2.5% for men. For women, more evidence of depressive symptoms was seen in the central region, whereas for men, symptoms were homogeneous across the country. Factors related to the presence of depressive symptoms include being divorced (in women) or widowed (in men), having lower educational attainment, perceiving one's place of residence as unsafe, displaying alcohol abuse or dependence, being a regular drug consumer (in men) and having been sexually abused (males and females). CONCLUSIONS: The regional distribution of depressive symptomatology in women indicates the need for region-specific prevention programs that take into account the different social problems that affect women's emotional well-being. More research is also needed to support the early identification and intervention of men suffering from depression.